Evaluation of CTEV Management in Children's Walking Ability Assessed by "BANGLA" Club Foot Tool Score System - Irfannuddin Irfannuddin; Nur Rachmat Lubis; Febian Aji Wicaksono (Bioscientia Medicina : Journal of Biomedicine and Translational Research, 2020)
Abstract Congenital talipes equinovarus (CTEV) or clubfoot is a congenital deformity that involves an abnormal position of the calcaneonaviculare complex. "Bangla clubfoot tool score system" is an assessment that indicates the effectiveness of CTEV management. The purpose of this study was to evaluate the management of CTEV on children's ability to walk as assessed by the Bangla clubfoot tool score system. A cross sectional study was conducted at the Hospital Dr. Mohammad Hoesin Palembang. There were 24 CTEV patients who received CTEV management before the age of 3 years and were not associated with a neurological disorder. A comparison of the average total Bangla clubfoot score tool system was analyzed by assessing parental satisfaction, walking ability and clinical examination. The majority of CTEV patients were women (58.3%) with and mostly being treated before 1 year old (79.2%). The most types of CTEV were bilateral (70.8%), and most of them performed surgery (66.7%). Assessment with the Bangla clubfoot tool system shows that the level of parental satisfaction is sufficient, gait is good, but physical foot examination is poor (20%). The score is influenced by age at first therapy and compliance using the brace. Parents must continue to support their children to undergo integrated management after therapy to maintain their walking ability.